Multiple endpoints of polylactic acid biomicroplastic toxicity in adult zebrafish (Danio rerio) - Chagas, Thales Quintao; Freitas, Italo Nascimento; Montalvao, Mateus Flores; Nobrega, Rafael Henrique [UNESP]; Ferreira Machado, Monica Rodrigues; Charlie-Silva, Ives; Costa Araujo, Amanda Pereira da; Batista Guimaraes, Abraao Tiago; Silva Alvarez, Tenilce Gabriela da; Malafaia, Guilherme (Elsevier B.V., 2021)
Although the toxicity of conventional microplastic types (i.e., petroleum derivatives) in different organisms is already known, knowledge about the effects of alternative biopolymers on aquatic vertebrates remains incipient. Thus, the aim of the present study is to test the hypothesis that the exposure of adult Danio rerio individuals to this pollutant for 30 days is enough to cause polylactic acid biomicroplastics (BioMPs of PLA) accumulation in their bodies, which leads to behavioral/neurotoxic, biochemical, and morphological changes. Based on our results, PLA BioMPs at concentrations of 2.5 and 5 mg/L accumulated in the liver, brain, gills and carcass of the assessed animals. However, such an accumulation was not able to cause locomotor damages or to trigger anxiety-like behavior in them. On the other hand, it was enough to cause behavioral changes (in shoal) predictive of co-specific social interaction and antipredatory defensive response deficit likely related to cholinergic changes inferred by increased acetylcholinesterase activity and REDOX imbalance. This imbalance was featured by increased production of reactive species. We observed that the treatments have affected animals' pigmentation pattern. Therefore, our study highlights the toxicological potential of the herein assessed biopolymer, and this finding puts in check the innocuousness of this material, as well as expands our knowledge about how PLA BioMPs can affect the ichthyofauna in freshwater environments. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: Biopolymers; Biomicroplastics; Fish; Behavioral toxicology